The Vegetation of the Mesters Vig District, Northeast Greenland. General Summary and Discussion. - Raup, Hugh M. (Meddelelser om Grønland, 1971)
Six generalized types of vegetation in the Mesters Vig district are described: moss-sedge meadow, heath tundra, heath-herb tundra, turf hummock vegetation, organic crust vegetation, and the vegetation of dry sites (ledges, talus, trap and till knolls, kames and emerged delta remnants). Lake and sea shore types have been described in an earlier paper, and are of minor significance in the landscape. The six types are analyzed with respect to habitat factors of ground coverage by vascular plants, moisture, and physical disturbance by frost and nonfrost geomorphic processes. Comparisons are made among the proportions of wide, intermediate and narrow tolerances to variations on these factor gradients exhibited by the species that compose the various types. It is proposed that with present knowledge of plant-site relationships the distribution of vascular species and vegetations can be rationalized for the most part in terms of the physical properties of the soil and the moisture supply. A key to the generalized types of vegetation is presented, based primarily on the interrelations of moisture, soil texture, and degree of ground coverage by vascular plants.